Design Prototype of Temperature and Humidity Control and Monitoring on Weaver Ant Cage based on Internet of Things - Dzata Farahiyah; Bevrin Wendra Purnama (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
Increasing market demand cannot meet the needs of the community, especially in the rainy season, because Kroto produced by weaver ants is of low quality and hard to find. Modern Kroto cultivation has many advantages compared to traditional searching in nature. The quality and quantity of Kroto lie in maintaining the temperature and humidity for weaver ants. The challenge is how to maintain the temperature and humidity inside the artificial nest of weaver ants. To help overcome the problems of modern weaver ant cultivation, we design and develop automated devices based on the Internet of Things (IoT) to control and monitor temperature and humidity for weaver ant culture. We chose the limitation of temperature is in between 25 oC – 31 oC, and the humidity range is on the level 65% - 85%. We used NodeMCU as the mainboard, DHT22 as temperature and humidity sensor, Cayenne webserver as IoT platform, and fan, humidifier, and heater for the tools to control the environment. We had conducted four tests scenario, which are sensor calibration, relay testing, actuator time testing, and delay testing. The result in temperature reading shows good accuracy while the humidity performs a huge gap of error. The humidity needs to be adjusted with the linear regression formula. Based on the relay testing, the device works perfectly fine to control the heater, the humidifier, and the fan. According to the actuator timing testing, the humidifier has the quickest time to make more humid and soothing conditions, around 5 – 15 minutes. In contrast, the heater actuator needs a longer time to heat up the room. Depends on the temperature, it needs around 5 – 31 minutes. The longest time was during the fan actuator to cool down the room, around 30 – 90 minutes. The average delay of the IoT system is 200,01 ms and is categorized as good performance based on standard TIPHON.